Navigating a shifting agri‐environment policy landscape to conserve butterflies. Issue 10 (20th August 2022) - Stewart, Linnea B.; Bonsall, Michael B.; Cusworth, George; Corrigan, Christopher; Dicks, Lynn V.; Hall, Jilly; Plackett, Jenny; Spray, Martin; Strevens, Chloë
Abstract: For decades, agri‐environment schemes (AES) within the United Kingdom have served as a policy tool for conserving butterflies. However, the UK's 2016 decision to leave the European Union (EU) means the overarching framework for AES, the EU Common Agriculture Policy (CAP), is being replaced by a new independent agri‐environment policy, the Environmental Land Management (ELM) scheme. Here, we examine the shift from CAP towards ELM and explore its implications for butterfly conservation across England, as a devolved administration, within the United Kingdom. We identify the key changes between the current Countryside Stewardship scheme and the incoming ELM scheme and present recommendations for policymakers to ensure policy design and delivery can benefit efforts to conserve butterflies, and indeed wildlife more generally, in England. This is an opportune moment to contribute to discussions on the emerging agri‐environment scheme policy within the United Kingdom as the ELM scheme is trialed, revised, and implemented.